Pemerolehan Bahasa Anak Usia 3 Tahun Studi Kasus : Evelyn Nasha Aprilia Putri - Khoirotunnisa; Velayati Khairiah Akbar (Universitas Nias, 2023)
This study aims to describe language acquisition in children aged 3 years, the subject of this research is Evelyn Nasha Aprilia Putri, 3 years old, who is placed in Turtle Daycare. Specifically covering the phonological and morphological levels. The method used in this research is descriptive qualitative method. Data collection was carried out using natural observation techniques, free-lance viewing, listening and daily notes. The results of this study indicate that the language acquisition of children aged 3 years is at the level of phonology and morphology. From a phonological point of view, the subject has mastered most of the consonant phonemes. But there are also phonemes that cannot be pronounced perfectly, 3-year-old children mostly omit or replace phonemes that should be there. This can be said to be reasonable, because at the age of 3 years the child's articulation tools and language mastery do not yet have. From a morphological point of view, the subject has mastered the word forms he has obtained, and the more words he says, and the arrangement of sentences is regular and longer, he can use three or more words, monomorphemic words are clear, morphemes can be seen that differentiate the meaning of words, there are free morphemes, bound morpheme, and affixation